Detection of influenza virus using peroxidase‐mimic of gold nanoparticles. Issue 10 (9th August 2016) - Ahmed, Syed Rahin; Kim, Jeonghyo; Suzuki, Tetsuro; Lee, Jaebeom; Park, Enoch Y.
ABSTRACT: A modified enzyme‐linked immunosorbent assay (ELISA) with nanomaterials is an effective and powerful method to amplify the signal and reduce the cost of detecting and measuring trace biomarkers or proteins. In this study, an ultra‐sensitive colorimetric immunoassay was designed, and its ability to detect influenza viruses using positively charged gold nanoparticles ((+)Au NPs) was assessed as a possible role for peroxidase‐mimic inorganic enzymes. This method detected influenza virus A (H1N1) with a linear range up to 10 pg mL −1 and clinically isolated influenza virus A (H3N2) up to 10 plaque forming units (PFU) mL −1, where its sensitivity improved to 500‐fold higher than that of commercial virus kits. The sensitivity of this proposed method was not declined even though in complex biological media in compared to conventional ELISA. These results revealed that the (+)AuNP‐based colorimetric immunoassay could be suitable for lab‐on‐a‐chip device and open new opportunities for clinical protein diagnostics. Biotechnol. Bioeng. 2016;113: 2298–2303. © 2016 Wiley Periodicals, Inc. Abstract : A novel colorimetric detection of influenza viruses was developed. Positively charged gold nanoparticles ((+)Au NPs) was used for catalyzing the H2 O2 ‐mediated oxidation of 3, 3′, 5, 5′‐tetramethylbenzidine instead of horseradish peroxidase. This method detected influenza virus A (H1N1) with a linear range up to 10 pg mL −1 and clinically isolated influenza virus A (H3N2) up to 10 plaque forming units (PFU) mL −1, where its sensitivity improved to 500‐fold higher than that of commercial diagnostic kit.